Pengaruh Instagram Online Store, Konformitas Dan Iklan Televisi Terhadap Perilaku Konsumtif Serta Dampaknya Terhadap Gaya Hidup Hedonis Mahasiswa - Wibowo, Bambang Setia (Jurnal Bisnis : Teori dan Implementasi, 2018)
This study examined the influence of instagram online store, conformity and television ads to consumptive behavior and its impact to student hedonic lifestyle. This study is the integration of previous studies to determine the effect of simultaneous  between variables. Respondents of this study were 142 university students respondents who have used social media instagram for online shopping, have a strong group of friends and know the television ads of fashion products. There are several findings in this study. First, instagram online store has positive influence to the consumptive behavior. Second, conformity has positive effect to consumptive behavior. Third, television ads has no effect to consumptive behavior. Fourth, consumptive behavior has  positive effect to student hedonic lifestyle.